(untitled) (Filološke pripombe, 2019)
This article is dedicated to the relation between onirism and the surrealistic poetic image which, seen from higher grounds, are closely interconnected. The etymological interpretation of dreaming indicates it is a specific state of the spirit that is characterised with hallucinative creations and disturbances of the realistic logical perception. Surrealism, on the other hand, is based on the belief in a higher reality of certain, already forgotten, forms of association, as well as on the belief in the power of dreams and the free word play. It is obvious that both of these phenomena are characterised by the unusual reality that is a result of a creation which inevitably contains inspiration as the initial imaginative process. What brings them closer together are also the common, easily recognisable mechanisms of reflecting, condensing, bridging, symbolizing, and other characteristics that can be found in both areas. It is what conditions their interconnection and this article shall illustrate it practically through the abundant poetry teeming with oniric surrealistic images written by Serbian, Macedonian and French poets (Milan Dedinac, Dushan Matich, Vlada Uroshevich, Mateja Matevski and Robert Desnos).